Assessment of infusion therapy impact on the dynamics of endothelin-1 in patients with acute ischemic stroke - A. I. Semenenko; N. O. Semenenko; Н. I. Hrebtii; S. L. Malуk; R. Ya. Bodnar; O. M. Hinhuliak (Zaporožskij Medicinskij Žurnal)
The impact of infusion solutions on endothelial damage correction in acute ischemic stroke (AIS) remains an insufficiently studied.